Recognition of the Existence of Traditional Legal Communities from the Perspective of Legal Philosophy - ADIYANTO, Bama; KRISTHY, Mutia Evi; MURTI, Jentung Wisnu; SALAHIDIN, Salahidin (Journal of Political And Legal Sovereignty, 2023)
Purpose - The existence of customary law communities occurs naturally, which has natural consequences for obtaining their rights. The granting of their rights as legal subjects must be based on genuine awareness that they have the right to obtain them, not motivated by compassion, which is preceded by requests or requests through violent movements. The state was obligated to maintain the living space of existing communities long before the Indonesian state was formed.Methodology - In this writing, the author uses normative juridical methods by studying customary law communities ontologically, epistemologically, and axiologically.Findings - Recognition of its existence should be followed by legal certainty. Constitutive recognition of the existence of customary law communities is necessary. The stipulation of the Law on Indigenous Peoples is a form of state action in interpreting justice, as stated by Ulpianus.Implication - The existence of customary law communities should be seen as a community whose existence is beyond doubt because it has been epistemologically tested concerning current reality.